(untitled) (Research, Society and Development, 2022)
Objective: To establish the level of physical activity and quality of life in teachers in the context of pandemic. Methodology: A descriptive, cross-sectional, cross-sectional design study was used for the investigation, with the participation of teachers and students in professional practice inserted in the educational system in times of pandemic. The physical activity level (GPAQ) and quality of life (WHOQOL-BREF) questionnaires were applied. SPSS 23.0 statistical software was used for statistical analysis and the data were stored with Excel. Results: When comparing the PA and QOL variables, it was deduced that there were no significant differences between the means of the groups according to PA; however, there was an upward trend which indicated that the higher the levels of physical activity, the better the quality of life of the teachers. Conclusion: Teachers who are physically active have a better QOL in all the domains presented compared to physically inactive teachers. This suggests physical activity as a means of protecting QOL.